An investigation into the genetic basis of anxiety - Dutton, R (2013)
This thesis aimed to investigate the genetic basis of anxiety in mice. The first half describes searches for genetic variation beneath quantitative trait loci (QTLs) and computationally pulls together data from several sources in order to assess how likely each variant is to be responsible for the QTLs. The second half describes the results of the behavioural phenotyping of three knockout mouse models. Examination of the sequence data beneath anxiety-related QTLs mapped from quasi-outbred mice identified 326 variants across eight inbred mouse strains in the coding and promoter regions beneath a prominent QTL for startle behaviour on murine chromosome 15. Variants in the genes Muc19, Gxylt1 and Kif21a were pinpointed as being most likely to contribute towards the phenotypic variation of that QTL. 12 structural variants (SVs) were also identified across the same strains as being potentially causal for at least one QTL when the search was extended to the whole genome. Testing the association between SV genotype and phenotype in an outbred murine population implied that SVs in the genes Fam110c, Fam117a and Gm6320 had similar phenotypic associations across different populations of mice, although the associations in the outbred mice did not achieve statistical significance. From the work with the three knockout mouse models, it was concluded that two of the genes, Eps15 and Car2, do affect anxiety in male animals, with Eps15 deficiency reducing anxiety and Car2 deficiency increasing it. The results for the Dstn mouse model were inconclusive. This model may need to be reengineered onto a less anxious background for future testing. In conclusion, this thesis identified a number of genes and genetic variants, some of which do seem to affect murine anxiety levels. Improved understanding of anxiety in mice will hopefully lead to a better understanding of the causes and treatment of anxiety disorders in humans.